1
$\begingroup$

Prove that if $ a \neq 0$ then $b/(b/a) = a$

Proof:

$ b/(b/a) = b. 1/(b/a)$ (by Multiplication Axiom 4 (M4))

$\implies b/(b/a) $ = $b.(b/a)^{-1}$ (by M5)

$\implies $ $b/(b/a)$ = $b.(b.(1/a))^{-1}$

$\implies $ $b/(b/a)$ = $b.(b.(a)^{-1})^{-1}$

$\implies $ $b/(b/a)$ = $b.[1/(b.(a)^{-1})]$

$\implies $ $b/(b/a)$ = $b . (1/b) . (1/a^{-1})$

$\implies $ $b/(b/a)$ = $1 .(1/a^{-1})$

$\implies $ $b/(b/a)$ = $(a^{-1})^{-1}$

$\implies $ $b/(b/a)$ = a

Is this correct? Can anyone please verify?

$\endgroup$
  • $\begingroup$ I'm just curious: where do you find the axioms? $\endgroup$ – GNUSupporter 8964民主女神 地下教會 Feb 11 '18 at 13:08
  • $\begingroup$ Do you mean derivation through axioms? $\endgroup$ – A.Asad Feb 11 '18 at 13:10
  • $\begingroup$ Though Rudia never used the notation $(\cdot)^{-1}$ is that section, but IMHO, I think it's fine if you write it as long as it means the inverse. In the second arrow, you used a property $(xy)^{-1} = x^{-1} y^{-1}$. This can be easily proven, by as a "proof" from the axioms (or the propositions from the book), I think it's better to mark every step, like this answer in set theory. $\endgroup$ – GNUSupporter 8964民主女神 地下教會 Feb 11 '18 at 13:18
  • $\begingroup$ Thank you, I'll do that (i.e. prove that $(xy)^{-1} = x^{-1} y^{-1}$ and mark my steps) . Is the proof fine otherwise? $\endgroup$ – A.Asad Feb 11 '18 at 13:25
  • $\begingroup$ Yes, I think so. $\endgroup$ – GNUSupporter 8964民主女神 地下教會 Feb 11 '18 at 13:27
1
$\begingroup$

As OP's comments suggest, to derive the proof from the five multiplication axioms in Baby Rudin, break $1$ into the product of $a$ and $1/a$ in the second step. $\require{action}$ $$ \begin{aligned} b / (b/a) &= \texttip{b \cdot 1 \cdot \left( \frac{1}{b/a} \right)} {(M4): multiplication by identity} \\ &= \texttip{b \cdot \left( \frac{1}{a} \right) \cdot a \cdot \left( \frac{1}{b/a} \right)} {(M5): existence of inverse} \\ &= \texttip{(b/a) \cdot a \cdot \left( \frac{1}{b/a} \right)} {(M3): regroup the leftmost two factors} \\ &= \texttip{a \cdot (b/a) \cdot \left( \frac{1}{b/a} \right)} {(M2): multiplication is commutative} \\ &= \texttip{a \cdot \left( (b/a) \cdot \left( \frac{1}{b/a} \right) \right)} {(M3): multiplication is associative} \\ &= \texttip{a \cdot 1}{(M5): multiplication by inverse} \\ &= \texttip{a}{(M4): multiplication by identity} \end{aligned} \bbox[4pt,border: 1px solid red]{ \begin{array}{l} \text{If you cannot figure out why a line}\\ \text{is true, move your mouse over}\\ \text{RHS of that line for hint.} \end{array}} $$ Remarks: The above proof is one line shorter than OP's one.

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.